Avaliação da resistência à compressão do concreto via ensaios não destrutivos : estudo comparativo - Beatriz Menezes Santos (2021)
The compressive strength of concrete is one of the most important and studied physical property worldwide, due to the fact that it is a characteristic that presents the bearing quality of the concrete part and is directly related to the structural safety and durability of a structure. The evolution of this property starts with the first crystals formed by the activation of the cement in contact with the water and goes until the completion of the formation of the hydration crystals in the concrete matrix. It is influenced by several factors, mainly by the design of the concrete mix, its constituent materials and the curing condition. In order to monitor whether this development is happening as projected, there is a rupture test by axial compression, in Brazil recommended by NBR 5.739. It is a destructive test, because the samples, taken to fatigue, can no longer be used after the test. At the same time, investigations about the quality of concretes, linked to other characteristics, such as their electrical resistivity or porosity, have been carried out through non-destructive tests, which bring indicative results of the development of these properties. The test results can bring to a conclusion the development of the compressive strength, as the investigated characteristics are often linked to the formation of hydration crystals or to the quality of the concrete microstructure. This dissertation presents the conclusions obtained from an experimental research about the development of the compressive strength of two types of concretes, in their early ages. One concrete was manufactured with CPV cement and the other with partial replacement in 20% of the cement by weight with metakaolin. The concretes were wet cured and tested at ages 12 and 24 hours, 7, 14 and 28 days after molding. Tests of axial compressive strength, superficial and volumetric electrical resistivity, elastic modulus of resonant frequency, ultrasound and sclerometry were performed. The data obtained were compared with the specific literature of each test method and it was also sought to correlate the results of the non-destructive tests with the compressive strength test in order to observe the existence of correlation between them. It was observed that the two types of concrete developed the compressive strength in a similar way, with very close values, and that the metakaolin did not have a great influence on the results in this percentage of material used, except in the results of electrical resistivity, where the concrete with metakaolin it was 400 times greater than the reference concrete at 28 days. In the other trials, such a difference was not observed. The correlations proposed between the compressive strength test and the electrical resistivity, ultrasound and sclerometry tests proved to be strong, equations were defined that best fit each type of test for the studied concretes, however there was no strong correlation between the compressive strength test and the dynamic modulus of elasticity, indicating that the development of the modulus of elasticity does not happen in a similar way to that of compressive strength.